Analisis Pencatatan dan Pelaporan PSAK 45 di Gereja X Salatiga - Edni Olka Pratiwi; Ika Kristianti (Jurnal Akuntansi, 2021)
Indonesia has already had an accounting standart for their non-profit organization, This standart are written in PSAK 45 about financial reporting for non-profit organization. This research are done in Gereja X Salatiga as a non-profit organization in religious organization. Aim of this research is to analyze application of PSAK 45 in Gereja X Salatiga financial report. This research is expected to help evaluate financial reporting in Gereja X Salatiga. Method used in this research are descriptive qualitative to describe, dechipher and compare data with circumstances and also explain such a situation so conclusions can be drawn. The results of this research is Gereja X Salatiga has implementing and using financial report suitable with PSAK 45, although its format are not following the format given bu Indonesian Accounting Association, but generally has reached its aim to report their financial process. Report shown to congregation are cash receipt and cash disbursement reports, and also a church expenditure receipt budget report. Keywords : PSAK 45, non-profit organization